2016
DOI: 10.1002/ejoc.201600332
|View full text |Cite
|
Sign up to set email alerts
|

A General and Mild Copper(I)‐Catalyzed Three‐Component Reaction of Cyanamides, Amines, and Diaryl­iodonium Triflates

Abstract: Abstract:A highly efficient copper-catalyzed three-component reaction of cyanamides, amines, and diaryliodonium triflates was developed for the synthesis of guanidines. The mild reaction accommodates both aromatic and aliphatic amines and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
6
0
1
Order By: Relevance
“…The stretching vibration absorption peak of NCO was found at 2276 cm −1 , and the absorption peaks at 2135 cm −1 are the NCN in substituted urea. The absorption peak at 1726 cm −1 is attributed to the CO carbonyl 35 . 1312 and 1226 cm −1 correspond to CN stretching vibrations on aromatic and aliphatic amines, respectively; the absorption peaks at 1112–1069 cm −1 are stretching vibrations of ether bonds (COC), indicating that both polyol and isocyanate in chitosan liquefaction are involved in the reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stretching vibration absorption peak of NCO was found at 2276 cm −1 , and the absorption peaks at 2135 cm −1 are the NCN in substituted urea. The absorption peak at 1726 cm −1 is attributed to the CO carbonyl 35 . 1312 and 1226 cm −1 correspond to CN stretching vibrations on aromatic and aliphatic amines, respectively; the absorption peaks at 1112–1069 cm −1 are stretching vibrations of ether bonds (COC), indicating that both polyol and isocyanate in chitosan liquefaction are involved in the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The absorption peak at 1726 cm À1 is attributed to the C O carbonyl. 35 1312 and 1226 cm À1 correspond to C N stretching vibrations on aromatic and aliphatic amines, respectively; the absorption peaks at 1112-1069 cm À1 are stretching vibrations of ether bonds (C O C), indicating that both polyol and isocyanate in chitosan liquefaction are involved in the reaction. Figure 1b illustrates the infrared spectra of the polymer-based foam materials.…”
Section: Structural Analysis Of Polymerbased Foam Materialsmentioning
confidence: 99%
“…为 了克服上述反应中存在缺点, 最近我们课题组以三氟甲 磺酸二芳基碘盐 58 为芳基化试剂, 发展了铜催化其和 氰胺 54 及胺 55 三组分反应高效构建胍 59 (Eq. 12) [31] . 相交于之前发展的铜催化硼酸的三组分反应 [30] 过渡金属催化氰胺和炔的环加成反应早在 1978 年 就已经有报道 [32] .…”
Section: 都具有良好的兼容性 反应可能经历以下反应历程: 钯unclassified
“…We also developed a copper-catalyzed three-component reaction of diaryliodonium triflates, cyanamides, and amines for the rapid synthesis of linear guanidines under mild reaction conditions. 16 To improve the atom-economy of this three-component reaction for the synthesis of 2-aminoimidazoles, a three-component cascade reaction of diaryliodonium triflates, cyanamides, and propargylamine was designed and investigated in this paper (Scheme 1). It was envisaged that propargylamine could undergo three-component guanidination with diaryliodonium triflates and cyanamides to generate propargylguanidines with the release of aryliodides under the catalysis of Cu I .…”
mentioning
confidence: 99%
“…The counter anion of diaryliodonium imposed a great influence on the reaction (Scheme S4a, ESI†) because the guanidination was subjected to the oxidative addition of the counter anion to Cu( i ). 16 Additionally, brief investigation showed that three-component atom-economical reaction of diaryliodonium triflates with cyanamides and propargylamine could ′not be realized even under relay catalysis of copper and palladium (Scheme S4b, ESI†).…”
mentioning
confidence: 99%